The main directions of modernisation of constitutional and legal responsibility in Ukraine - Lutskyy, Andriy; Lutskyi, Myroslav; Kaleniuk, Oksana; Zvarych, Roman; Knysh, Vitalii (International Journal of Psychosocial Rehabilitation, 2020)
The article is dedicated to the latest forms and types of constitutional liability in Ukraine. The main focus is pointed to such forms and types as lustration, decommunization and decentralization of authorities and local self-government. The research methods are based on the results of scientific studies of Ukrainian and foreign scientists on the problems of constitutional responsibility in Ukraine and the world. To justify the fullness and reliability of obtained results, the authors used the method of dialectics, regulatory-dogmatic, system-structural, system-functional methods, as well as method of generalization. According to the authors, the mechanism of constitutional liability implies, on the one hand, an even distribution of positive responsibility between the central state authorities and local authorities and self-government, and on the other hand, it implies their negative liability in the event of going beyond their autonomous powers. Moreover, in order to ensure the mutual accountability of the Parliament and the Government, they have both established the possibility of mutual application of influential measures (the possibility of dissolution of Parliament and the resignation of the Government).